A Single‐Atom Nanozyme for Wound Disinfection Applications. (5th March 2019) - Xu, Bolong; Wang, Hui; Wang, Weiwei; Gao, Lizeng; Li, Shanshan; Pan, Xueting; Wang, Hongyu; Yang, Hailong; Meng, Xiangqin; Wu, Qiuwen; Zheng, Lirong; Chen, Shenming; et al.
Abstract: Single‐atom catalysts (SACs), as homogeneous catalysts, have been widely explored for chemical catalysis. However, few studies focus on the applications of SACs in enzymatic catalysis. Herein, we report that a zinc‐based zeolitic‐imidazolate‐framework (ZIF‐8)‐derived carbon nanomaterial containing atomically dispersed zinc atoms can serve as a highly efficient single‐atom peroxidase mimic. To reveal its structure–activity relationship, the structural evolution of the single‐atom nanozyme (SAzyme) was systematically investigated. Furthermore, the coordinatively unsaturated active zinc sites and catalytic mechanism of the SAzyme are disclosed using density functional theory (DFT) calculations. The SAzyme, with high therapeutic effect and biosafety, shows great promises for wound antibacterial applications.